(untitled) (Journal of the College of Basic Education, 2022)
Physics is one of the important scientific subjects in human life, and like other branches of science, it contains many concepts that are difficult to understand if presented in an abstract way. .The process of teaching physics currently needs development and improvement, as the reality of this process traditionally still depends on narration and indoctrination. (Beichnen, 1996: 1274)That is, there is a need to teach physics related to the transfer of knowledge from the abstract to the tangible.